The Concept of Rebellion/Rebel in the Behistun Inscription: Formal Terminology and Phrases - Adel Allahyari; Assistant Professor Hossein Badamchi (پژوهش های تاریخی)
AbstractThe main issue of the present research is the nature of the concept of rebellion (rebel) in the Behistun Inscription. To answer this question, the study utilizes a conceptual historical method based on analyzing the Old Persian text of the Behistun Inscription, focusing on the words or phrases used to denote the concept of rebellion.The research findings indicate that the Behistun Inscription employs words and phrases to represent the concept of rebellion, where understanding some terms requires knowledge of their prior usage in the tradition of Mesopotamian kings, especially in Neo-Assyria. However, the omission of certain terms and the simultaneous use of new phrases in the fifth column of the inscription suggest a transformation in Achaemenid political thought regarding how the concept of rebellion is represented.Nevertheless, all words and phrases representing the concept of rebellion in the Behistun Inscription share a common characteristic regarding the essence of this concept in Achaemenid political thought, which is the issue of breaking loyalty to the Achaemenid king; "oath-breaking".Keywords: Arīka, Lie, Behistun Inscription, Concept of Rebel/Rebellion, Oath-breaking.IntroductionThe Behistun Inscription is the most significant surviving document from the ancient Near East and one of the earliest records in Iranian languages. It stands as the sole Old Persian inscription that explicitly details political events. According to the text, on the 10th day of the month Bāgayādai̭š (September 29) in 522 BCE, Darius I, son of Hystaspes of the Achaemenid dynasty, with the aid of Ahuramazdā and accompanied by 6 prominent Persian nobles, killed Gaumata the Magus. Gaumata had usurped the throne, falsely claiming to be Bardiya, son of Cyrus, in a castle located in Media. This act ignited widespread revolts against Darius's rule in regions, including Elam, Babylon, Persia, Media, Assyria, Egypt, Parthia, Merv, Susa, and Scythia.  In response, Darius, supported by Ahuramazdā and his Persian and Median forces, quashed all rebellions within a year, achieving victory in 19 battles. During this campaign, he captured and punished 9 rebel leaders. Following these events, Darius commissioned the creation of the Behistun Inscription and its relief to assert his legitimacy, detailing the reasons and methods of his ascension to the Achaemenid throne. This document employed specific and significant vocabulary to articulate the concept of rebellion. However, this raised an important question: do the terms and phrases used by the Achaemenid king to depict rebellion convey the same meanings that we understand today?Materials & MethodsThis research sought to elucidate the meaning of the concept of "rebellion" (or "rebel") in the Behistun Inscription by employing the method of "conceptual history". At its core, conceptual history examines the evolution and significance of words. However, these words, which we categorize as concepts, possess distinct characteristics. Concepts are semantically richer, more ambiguous, and inherently more contentious than words that simply denote specific objects in the material world (Jordheim, 2021, p. 1). In essence, while the meaning of a word can be precisely defined, concepts are subject to interpretation (Koselleck, 1972, p. XXIII). The conceptual history method strives to bridge the gap between the history of ancient ideas and modern intellectual discourse through linguistic analysis (Clark, 2018, p. 161). As Koselleck articulates, conceptual history "begins the image of history through its fundamental concepts and understands these concepts historically", stressing that its primary focus is on "the convergence of concepts and history" (Koselleck, 2011, p. 21). In this method, it is essential to consider the social context, in which a concept is employed to fully understand its implications (Koselleck, 2002, p. 20). Regardless of how we define conceptual history, a focus on language—particularly vocabulary and its semantic content—is crucial. Koselleck, however, underscores that in conceptual history, "concepts are examined based on their socio-political functions rather than their linguistic ones" (Koselleck, 2011, p. 18). Building on these insights, this research focused on the words and phrases used to denote the concept of "rebellion" (or "rebel") in the Old Persian text of the Behistun Inscription, employing the method of conceptual history. It also examined how these terms functioned within the text and compared them to their equivalents, particularly in the Akkadian version. This approach aimed to illustrate the historical context and semantic ranges of these concepts, along with similar examples from the records of Mesopotamian kings.Research FindingsThe examination of the concept of rebellion in the Behistun Inscription revealed significant insights into Achaemenid political thought and terminology. By analyzing the Old Persian text, we identified key terms and phrases that illustrated how rebellion was understood and articulated in this historical context.The analysis highlighted specific vocabulary employed in the first 4 columns of the Behistun Inscription, including "arīka", "draṷga", "udapatatā", and "hamiçiya". Each term carried distinct connotations that reflected the socio-political landscape of the Achaemenid Empire."Arīka": This term functioned as a general descriptor for individuals, who had forsaken their loyalty to the Achaemenid king. Its comparison with the Akkadian equivalent lib-bi [bi-i]-šú showed that "arīka" denoted a serious breach of allegiance, reinforcing the political significance of loyalty in Achaemenid ideology."Draṷga": Analyzing this term in the context of ancient Near Eastern traditions, particularly concerning the motif of "lie", revealed its dual role as both a political and cultural concept. The omission of "draṷga" in the 5th column might indicate a shift in the Achaemenid narrative surrounding rebellion, suggesting that political discourse evolved over time as influenced by Mesopotamian royal traditions."Udapatatā": Translated as "to rebel," this term’s usage in the Behistun Inscription described the formation and leadership of rebellions. However, its application was nuanced as it conveyed more than mere insurrection; it implied a complex interplay of authority and rebellion."Hamiçiya": Typically rendered as "rebel" or "enemy", this term encompassed individuals, who had previously pledged loyalty to the Achaemenid king but later betrayed that allegiance. Its relationship with the Akkadian term "nakāru" suggested that "hamiçiya" specifically referred to "oath-breakers", emphasizing the importance of loyalty in Achaemenid political ideology.The 5th column of the Behistun Inscription continued to address the theme of rebellion but marked a notable departure from the first 4 columns. The phrase "nai Auramazdašām ayadiya", which translated to "those who do not praise Ahuramazdā", suggested a deeper theological dimension to rebellion. This shift implied that rebellion was not only a political act, but also a spiritual one, involving a violation of loyalty to both the king and the divine.Across the various terms and phrases analyzed, a central theme emerged: the concept of "oath-breaking" was pivotal to understanding rebellion within the Achaemenid framework. The consistent focus on loyalty and the consequences of betrayal reinforced the ideological underpinnings of Achaemenid governance. This perspective positioned rebellion not merely as a challenge to authority, but as a profound moral and social failing.Discussion of Results & ConclusionThe findings of this research revealed that the vocabulary used to represent the concept of rebellion in the political thought of the Achaemenid Empire, particularly in the first 4 columns of the Behistun Inscription, included terms, such as "arīka", "draṷgā", "udapatatā", and "hamiçiya".An analysis of the term "arīka", in comparison with its Akkadian equivalent (lib-bi [bi-i]-šú), indicated that "arīka" functioned as a general concept with political significance, referring to individuals, who had abandoned their loyalty to the Achaemenid king and turned against him.The term "draṷga", when examined in the context of the historical motif of "lie" as it pertained to the concept of rebellion in ancient Near Eastern traditions, revealed that its application in the Behistun Inscription—and its omission in the 5th column—suggested that this concept not only served a political function, but was also likely influenced by the traditions of Mesopotamian kings, particularly those of Neo-Assyria.Furthermore, the translation of "udapatatā" as "to rebel" appeared to be inadequate. In the context of the Behistun Inscription, "udapatatā" was used to describe the formation of rebellion and introduce its leader and his claims.On the other hand, the term "hamiçiya", which was typically translated as "rebel" and sometimes as "enemy", did not accurately convey its meaning when considered alongside its Akkadian equivalent in the Behistun Inscription (nakāru). This was because "nakāru" could signify both "enemy" and "rebel" depending on the textual context. In fact, Old Persian inscriptions employ other terms, such as "paratara" and "hai̭na", specifically to denote the concept of "enemy".  Thus, in the context of the Behistun Inscription, "hamiçiya" referred to individuals, who had previously pledged loyalty to the Achaemenid king but subsequently broke their oath and allied with others against him. They were better described as "rebels" or, more accurately, "oath-breakers".The results of this research indicated that the 5th column of the Behistun Inscription, like the first 4 columns, addressed the issue of "rebellion". However, the omission of the motif of "lie" in this section replaced by the phrase "nai Auramazdašām ayadiya" suggested a shift in Achaemenid political thought regarding the representation of rebellion. The phrase "those who do not praise Ahuramazdā" likely alluded to a prior oath of loyalty made in the name of Ahuramazdā and towards the Achaemenid king. Thus, "those who did not praise Ahuramazdā" could be understood as individuals, who had violated their oath of loyalty to the Achaemenid king.In conclusion, all the words and phrases representing the concept of rebellion in the Behistun Inscription shared a common theme within Achaemenid political thought: the issue of breaking one's oath of loyalty to the Achaemenid king encapsulated in the concept of "oath-breaking".